THE CURRENT STATUS OF ANTIRETROVIRAL THERAPY ADHERENCE AMONG OUTPATIENTS WITH HIV/AIDS AT GIA RAI REGIONAL HEALTH CENTER, CA MAU PROVINCE, IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of antiretroviral therapy adherence among outpatients with HIV/AIDS at Gia Rai regional Health Center, Ca Mau province in 2025.Methods: A cross-sectional study was conducted among people living with HIV who were receiving antiretroviral therapy at Gia Rai regional Health Center, Ca Mau province in 2025.Results: The study included 345 HIV/AIDS outpatients receiving antiretroviral therapy at Gia Rai regional Health Center. The results showed that the antiretroviral therapy adherence rate was 68.1%, while 31.9% were non-adherent. Most participants had adequate knowledge of antiretroviral therapy treatment (74.2%). Factors significantly associated with treatment adherence included educational level, knowledge about treatment, frequency of counseling, drug side effects, fear of disclosure, and the use of medication reminders (p < 0.05). Patients who received regular counseling, had correct knowledge about antiretroviral therapy, and used medication reminder methods had higher adherence rates.Conclusion: The study showed that the antiretroviral therapy adherence rate among patients was 68.1%, indicating a relatively moderate level of adherence. Treatment adherence was significantly associated with gender, educational level, treatment knowledge, counseling frequency, drug side effects, fear of disclosure, and medication reminder methods. The findings highlight the important role of counseling, improving patient knowledge, and supporting medication reminders in maintaining antiretroviral therapy adherence. Strengthening patient support interventions is therefore necessary to improve treatment outcomes and HIV/AIDS control at the local level.
Keywords: HIV/AIDS, antiretroviral therapy, treatment adherence, people living with HIV, associated factors, outpatient care, Gia Rai regional Health Center.